PENGARUH PENGELUARAN PEMERINTAH TERHADAP INVESTASI DAERAH SUMATERA UTARA - ENNI SARI SIREGAR (Jurnal Education and Development, 2016)
This article focused on analyze effect of the goverment expenditure to investment in North Sumatera. Data used time series of 1982-2012. This article use analyzer model equation with method of analysis using the correlation formula "r" by Pearson product moment. The result of research concludes that the goverment expenditure is significant and negative effect on the investment in North Sumatera. Based on calculations performed obtained rhitung = 0.368. When compared with rtabel at 95% confidence level or error rate of 5% with degrees of freedom (df) = N-nr=31-2=29, obtained rtabel of 0.367. It is proved that the value rhitung > rtabel is 0.368 > 0.367. In other words, goverment expenditure have effect to investment in North Sumatera.